THE KUPATAN TRADITION IN TIRTA MULYA VILLAGE IN THE FORM OF A DOCUDRAMA FILM - Rusnia Transawitri; Yusril (Journal of Social Science, 2026)
Objective:  The objective of presenting the Kupatan tradition through a docudrama film format is to disseminate information and encourage community reflection on the practice. Method: The selection of a docudrama as the medium is predicated on its capacity to visually and audibly depict communal activities, while simultaneously offering participants a novel experiential opportunity in the filmmaking process. The docudrama employs an essayistic approach to its narrative structure, enabling comprehensive coverage of events organized either chronologically or thematically. The pre-production phase involves detailed planning and preparation related to the production process, whereas the production phase constitutes the execution of these plans. Results: The Kupatan tradition is a cultural practice observed by the Javanese community on the seventh day following Eid al-Fitr. This tradition involves serving ketupat snacks as part of the kenduri ceremony, alongside activities such as fostering social ties, almsgiving, and mutual forgiveness, which collectively embody the symbolic significance of Kupatan. Novelty: The selection of a docudrama as the medium is predicated on its capacity to visually and audibly depict communal activities, while simultaneously offering participants a novel experiential opportunity in the filmmaking process.